PELATIHAN DAN PENDAMPINGAN PENGELOLAAN KEUANGAN DAN OPTIMALISASI USAHA PADA CV ZERONE - Izza Ashsifa; Muhammad Teguh Kuncoro (COMMENT: Journal of Community Empowerment, 2022)
The challenges for Micro, Small and Medium Enterprises (MSMEs) are getting bigger as a result of the complex economic environment. MSMEs need to have good financial management skills. Financial management is an important element of overall business management. With financial management, MSMEs can make decisions about inventory planning and pricing, sufficient cash flow to maintain business operations and for better business forecasting and projections. Effective financial management will affect the overall profit of MSMEs. Financial management through the preparation of financial reports will have a positive impact on MSMEs in optimizing their business in the long term.This community service program is designed to provide solutions and assist CV Zerone in conducting financial management. This community service program is carried out because there is no comprehensive financial reporting system at CV Zerone so that owners have difficulty measuring the company's financial performance. This activity is carried out by providing training and assistance in making financial reports. The objectives of this community service program are: 1) providing education on the importance of financial reports for the company, 2) assisting CV Zerone in preparing comprehensive financial reports to show financial performance, 3) assisting CV Zerone in analyzing financial reports to improve company performance. This community service program makes CV Zerone able to make comprehensive financial reports, gain skills to analyze the results of financial reports and be able to make strategic decisions to optimize its financial performance.